Drug resistance and genotyping studies of Salmonella Enteritidis isolated from broiler chickens in Iran - Piryaei, Mohammad Reza; Peighambari, Seyed Mostafa; Razmyar, Jamshid (Frontiers in Veterinary Science, 2025)
IntroductionPoultry products are considered an important source of Salmonella infections. Transmission of non-typhoidal Salmonella enterica serovars to humans has been a great concern worldwide. Occurrence of multi-drug resistance, adding to the presence of various virulence factors, which facilitate the pathogenesis of Salmonella, would cause tremendous risk for both human and animals’ health.Methods and resultsDuring 2023, out of a total number of 1,274 samples from broilers in Iran, 114 isolates of Salmonella spp. (8.94%) were detected from which 97 isolates were confirmed as Salmonella Enteritidis (SE). Eight virulence genes including invA, sefA, sopE, spvC, hilA, agfA, sivH and lpfA, were detected among SE isolates and it was found that all isolates harbored these genes at the rate of 100% except for spvC, which was present in 96.90% of the SE isolates. In phenotypic evaluation of resistance against 16 antimicrobial agents, high resistance rates were observed against nalidixic acid, ampicillin, amoxicillin–clavulanate and ciprofloxacin. While resistance to tetracycline, streptomycin and chloramphenicol was found to be moderate, it was very low to azithromycin, sulfamethoxazole-trimethoprim, amikacin, gentamicin, ceftriaxone and cefotaxime. However, all isolates were sensitive to meropenem, ceftazidime and aztreonam. The mean of MAR index values was 0.26 and 72.15% of the isolates were found to be highly resistant. In detection of 14 resistance genes among SE isolates, five genes including blaTEM, tetA, tetB, sul1 and strA/B were found with prevalence rates of 63.92, 36.08, 61.85, 10.30 and 14.43%, respectively.DiscussionThe high prevalence rates of MDR in SE, along with the overwhelming presence of major virulence factors raise public health concerns. These data highlight the great potential risks of the presence and transmission of highly pathogenic MDR Salmonella to humans from chicken meat sources, as well as the need for more effective surveillance for antimicrobial use in the poultry industry. Reducing/optimizing the use of antimicrobials, improving poultry management procedures, using probiotics and biosecurity or vaccines are essential to deal with this issue.